A hybrid analytical–numerical method for computing coupled temperature and moisture content fields in porous soils. (July 2018) - Gasparin, Suelen; Chhay, Marx; Berger, Julien; Mendes, Nathan
This work is devoted to proposing a hybrid numerical–analytical method to address the problem of heat and moisture transfer in porous soils. Several numerical and analytical models have been used to study heat and moisture transfer. The complexity of the coupled transfer in soils is such that analytical solutions exist only for limited problems, while numerical solutions can deal with more realistic ones but at a higher computational cost. Therefore, we propose to implement analytical solutions where variations of temperature and moisture content are known to be almost nonvarying, while the numerical solution is implemented in the remaining region, near the boundaries. The coupling between solutions is performed assuming the continuity of both fields and fluxes at each interface. This strategy allows assuring the physical phenomenon occurring at the interface. Numerical experiments are performed, showing the accuracy, the efficiency, and the great potential of the method regarding applications in nonlinear soil problems.